2016
DOI: 10.1091/mbc.e15-09-0631
|View full text |Cite
|
Sign up to set email alerts
|

Auxilin facilitates membrane traffic in the early secretory pathway

Abstract: In this study, a proteomic approach links the J-domain chaperone auxilin, which uncoats clathrin-coated vesicles, to the other major coat complexes in the cell (COPII and COPI). Genetic and biochemical studies support the proposal that auxilin facilitates vesicle traffic in the early secretory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…First, similar to other cargo receptors it cycles between the ER and Golgi and is affected by Sec24 cargo‐binding site mutants. In support of our findings, Exp1 was found to be enriched in COPI/COPII vesicles in 2 independent studies and we found that it is packaged into COPII vesicles in vitro. Second, Exp1 physically binds Pma1 as would be expected for a cargo receptor.…”
Section: Discussionsupporting
confidence: 90%
“…First, similar to other cargo receptors it cycles between the ER and Golgi and is affected by Sec24 cargo‐binding site mutants. In support of our findings, Exp1 was found to be enriched in COPI/COPII vesicles in 2 independent studies and we found that it is packaged into COPII vesicles in vitro. Second, Exp1 physically binds Pma1 as would be expected for a cargo receptor.…”
Section: Discussionsupporting
confidence: 90%
“…We were unable to express full length LdSec24 and LdSec31 in E. coli as observed previously (54). Therefore, LdSec31…”
Section: Generation and Purification Of Different Mutants Of Copii Prmentioning
confidence: 69%
“…This is in contrast to loss-of-function alleles of other endocytic components, which exhibit various defects in growth, development, and/or reduced fertility (Gadeyne et al, 2014;Kang et al, 2001Kang et al, , 2003Collings et al, 2008;Kim et al, 2013;Kitakura et al, 2011). This observation also differs from that of auxilin loss-of-function mutants in yeast, whose growth is reduced (Ding et al, 2015), and auxilin/GAK lossof-function mutants in animals such as mouse, worm, or zebra fish, where various aspects of development are affected (Yim et al, 2010;Greener et al, 2001;Bai et al, 2010;Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 88%